2014
DOI: 10.1038/ki.2013.530
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vitamin K recycling in uremia is rescued by vitamin K supplementation

Abstract: In chronic kidney disease, vitamin K-dependent proteins, including the calcification inhibitor matrix Gla protein, are largely uncarboxylated indicating that functional vitamin K deficiency may contribute to uremic vascular calcification. Since the effects of uremia on the vitamin K cycle are unknown, we investigated the influence of uremia and vitamin K supplementation on the activity of the vitamin K cycle and extraosseous calcification. Uremia was induced in rats by an adenine-supplemented diet and vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 37 publications
(32 reference statements)
1
78
0
1
Order By: Relevance
“…To the best of our knowledge, no previous study has directly measured vitamin K epoxides in tissues from a CKD model. Using microsomal protein derived from tissue from an adenine CKD model, Kaesler et al [9] measured VKOR activity and found no difference between CKD and control animals. They did, however, report that the activity of the vitamin K cycle enzyme GGCX was reduced in both the kidney and aorta, and that this could be overcome by increasing the amount of vitamin K in the diet [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, no previous study has directly measured vitamin K epoxides in tissues from a CKD model. Using microsomal protein derived from tissue from an adenine CKD model, Kaesler et al [9] measured VKOR activity and found no difference between CKD and control animals. They did, however, report that the activity of the vitamin K cycle enzyme GGCX was reduced in both the kidney and aorta, and that this could be overcome by increasing the amount of vitamin K in the diet [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K treatment has been shown to attenuate CKD-induced vascular calcification in 2 separate pre-clinical studies. Work from our laboratory and Kaesler et al reported that high dietary vitamin K decreased susceptibility to calcification in an adenine-induced model of CKD [8,9] . The impact on humans with CKD is currently being tested in 2 large randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin K is essential to turn uncarboxylated MGP into carboxylated MGP, which enables the protein to gain inhibited function (90). In uremic rats induced by adenine, Kaesler et al (35) found vitamin K deficiency measured by its impaired ␥-carboxylase activity, accompanied with an increase of AC after 7 wk. Pharmacological vitamin K supplementation restored plasma carboxylated MGP concentrations and slowed development of AC (35).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%
“…In uremic rats induced by adenine, Kaesler et al (35) found vitamin K deficiency measured by its impaired ␥-carboxylase activity, accompanied with an increase of AC after 7 wk. Pharmacological vitamin K supplementation restored plasma carboxylated MGP concentrations and slowed development of AC (35). Moreover, in a randomized, controlled trial involving 53 hemodialysis patients, Westenfeld et al (104) demonstrated that daily vitamin K supplementation for 6 wk significantly improved MGP bioactivity and ameliorated AC.…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%